2011
DOI: 10.1007/s10641-011-9890-3
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal trends in stable carbon and oxygen isotope ratios of juvenile winter flounder otoliths

Abstract: Isotopic ratios of fish otoliths have been used in numerous studies as natural tags or markers to aid in the study of connectivity among fish populations. We investigated the use of spatial and temporal changes in the stable carbon and oxygen isotope ratios of otoliths to differentiate juvenile habitats of winter flounder (Pseudopleuronectes americanus). Young-of-the-year (YOY) juvenile winter flounder were collected annually over a three-year period from 18 stations along the coast of Rhode Island, USA. Sagit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…These sampling locations included three shallow coastal lagoons, which are locally called salt ponds (Point Judith Pond, Ninigret Pond and Green Hill Pond), an estuarine river system (Narrow River) and the upper, middle and lower portions of Narragansett Bay (Figure 1). Details on the locations and physical characteristics of these stations are included in previous publications (Pruell et al 2012;Pruell and Taplin 2015). Figure 1 provides information on the locations and discharge flows (averaged from 2002 -2004) from the WWTFs in the Narragansett Bay watershed.…”
Section: Fish Collectionmentioning
confidence: 99%
“…These sampling locations included three shallow coastal lagoons, which are locally called salt ponds (Point Judith Pond, Ninigret Pond and Green Hill Pond), an estuarine river system (Narrow River) and the upper, middle and lower portions of Narragansett Bay (Figure 1). Details on the locations and physical characteristics of these stations are included in previous publications (Pruell et al 2012;Pruell and Taplin 2015). Figure 1 provides information on the locations and discharge flows (averaged from 2002 -2004) from the WWTFs in the Narragansett Bay watershed.…”
Section: Fish Collectionmentioning
confidence: 99%
“…There has been considerable research on the geographical variation of natal geochemical signatures, but limited studies have examined the temporal stability of otolith chemistry. Studies that examined temporal variation in otolith chemical composition found substantial variations within (Thorrold and Shuttleworth 2000;Reis-Santos et al 2012) and among years (Campana et al 2000;Gillanders 2002;Walther and Thorrold 2009;Pruell et al 2012), which could lead to misinterpretation of spatial variability in otolith signatures (Reis-Santos et al 2012;Avigliano et al 2018). For instance, in Platichthys flesus (Linnaeus, 1758) and Dicentrarchus labrax (Linnaeus, 1758), collected from several estuaries along the Portuguese coast in two years and three seasons within a year, significant differences were observed in the majority of otolith elements among estuaries and sampling times, which were likely to be a reflection of the observed variability in environmental conditions, incorporating seasonal variation, which resulted in an 11% increase in the correct classification of individual estuaries (Reis-Santos et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There was some overlap in elemental fingerprints among years for different estuaries for juvenile snapper Pagrus auratus (Forster, 1801), which was likely to have consequences in the assignment of adult fish to recruitment estuaries, especially if juvenile fish were collected from different estuaries in different years and adult fish were not assigned to recruitment estuaries using elemental fingerprints from the year class of recruits in which they were juveniles (Gillanders 2002). Furthermore, the long-term stability of otolith chemical signatures has been less frequently investigated (Avigliano et al 2018), suggesting that chemical signatures may serve only as shortterm natural tags (1-3 y) (Rooker et al 2001;Walther and Thorrold 2009;Pruell et al 2012).…”
Section: Introductionmentioning
confidence: 99%